HIV risk and pre-exposure prophylaxis interest among female bar workers in Dar es Salaam: cross-sectional survey - Harling, Guy; Muya, Aisa; Ortblad, Katrina F.; Mashasi, Irene; Dambach, Peter; Ulenga, Nzovu; Barnhart, Dale A.; Mboggo, Eric; Oldenburg, Catherine E.; Bärnighausen, Till; Spiegelman, Donna (BMJ open, 2019)
Objective Female bar workers (FBW) in East Africa often conduct sex work to supplement their incomes, and may be vulnerable to HIV acquisition. Pre-exposure prophylaxis (PrEP) offers protection against HIV acquisition. However, there is little research on FBW's sexual health. Our objective was to determine HIV risk behaviours and interest in PrEP among FBW in the largest city in East Africa. Design Cross-sectional survey covering respondents' work and personal lives, including social and behavioural risk factors for HIV. The survey aimed to determine the feasibility of working with FBW and HIV prevalence estimates. Those who did not report being HIV positive were asked about their knowledge of and interest in PrEP. All women were offered free on-site HIV testing and counselling (HTC). Setting Eight randomly selected workplaces, that is, bars, in Kinondoni district, Dar es Salaam (DSM). Participants 66 FBW (= 18 years) selected at random from all women working in selected bars on the day of visit. Results Half of respondents reported having had sex for money: 20% with bar clients only, 15% with other men only and 15% with both. Almost all (98%) reported = 1 non-commercial partners in the past 12 months; only 30% reported using condoms with these partners. 85% of respondents had ever been pregnant; 44% had had an unintended pregnancy. Only 5% of respondents had ever heard of PrEP. However, 54% were somewhat/very interested in daily-pill PrEP and 79% were somewhat/ very interested in long-acting injectable PrEP. When asked to rank modalities, long-acting injectable PrEP was the most preferred. Seven per cent of the 56 respondents who completed HTC tested HIV positive. Conclusions FBW in DSM have elevated risk factors for HIV acquisition, and PrEP appears highly acceptable. Studies developing PrEP delivery models and assessing PrEP initiation and adherence in FBW appear warranted.